Charge induced reconstruction of glide partial dislocations and electronic properties in GaN. (15th January 2022) - Huang, Lili; Wu, Xiaozhi; Zou, Yongtao; Li, Mu; Wang, Rui
Graphical abstract: Abstract: Dislocations have been thought to generate significant effects on the performance of GaN-based devices. The intensive studies have usually focused on threading dislocations on the prismatic or pyramidal planes of wurtzite GaN. Here, we alternatively investigate the partial dislocations on the basal plane of GaN. By a combination of the fully discrete Peierls theory and first-principles calculations, the core structures and electronic properties of 90°/30° partial dislocations with glide-sets have been obtained. From the analytical displacement fields, we show that the single-period and double-period reconstructions of the partial dislocations are present. Importantly, due to the intrinsic polarity of dislocation cores, the introduction of excess charge is uncovered to strongly affect the reconstructions, exhibiting unique charge-induced structural transitions. Furthermore, the electronic density of states indicate that the stable reconstructed structures possess the defect levels inside the bulk gaps, which are localized along the dislocation lines at core regions. Our work not only extends the understanding of dislocations and their related properties in GaN but also offers fascinating guidance for designing GaN-based devices.